Representasi Ideologi dalam Kaidah Tafsir - Fatihullah, Fatihullah (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2018)
This paper discusses al-QawaÌâid al-HÌ£isaÌn li-TafsiÌr al-Qurâanwritten by al-Saâdi, a work with a particular format talking about interpretation rule. The interpretation rules are like a helpful tool to come with the Quran and its interpretation as such that its users can avoid from the mistake and differentiate which one is acceptable and rejected. As a tool to understand the Quran, the interpretation rule is essentially similar with usul fiqh (legal rule) in its formulation that must be scientific (verifiable), critical (non-sectarian) and objective (nonideological). This research proves that the listed rules of interpretation in al-QawaÌâid al-HÌ£isaÌn li-TafsiÌr al-Qurâanare not purely theoretical-objective rules, rather represent al-Saâdiâs ideological and subjective nuances.